National Geographic Magazine [computer file] The 1950s (vol. CXVI, no. 5, November 1959)1950-April 1953, May 1953-August 1956, September 1956-December 1959 (Washington, CD National Geographic Society, 1888)
Endure humanity's first cruel winter at the South Pole, as a team of scientists battles temperatures of 100 fahrenheit below zero. Explore the world's vast oceans with Captain Jacques-Yves Cousteau and his revolutionary Aqua-lung". Thrill to the conquest of Mount Everest in 1954. Discover the wreck of the Bountry and meet the direct descendants of Fletcher Christian and his crew. And experience many more captivating.
California's Wonderful One, Searching for Cliff Dweller's Secrets, Boom Days in the Southwest, Tukuna Maidens Come of Age, Whooping Cranes Fight for Survival, Seychelles, Tropic Isles of Eden, 1960 Census: Profile of the Nation
The complete National Geographic on CD-ROM was produced from archive of magazines collected in a central repository and is not representative of any single regional edition of National Geographic magazine.
Minimum requirements for Windows: Pentium 90MHz or faster, 24MB RAM, 70MB free hard-disk space, SVGA video card supporting 16-bit color, 16-bit sound card and speakers, 4x CD-ROM drive.
Minimum requirements for Macintosh: PowerPC or higher, System 7.5 or higher, 32MB RAM, 70MB free hard-disk space, 640x840 16-bit color monitor, 4x CD-ROM drive.
Keywords: Mount Everest